OCP Java SE 6 programmer practice exams, exam 310-065 - Bates, Bert; Sierra, Kathy (New York McGraw-Hill, 2011)
"Don't Let the Real Test Be Your First Test! Written by two of the lead developers of the Java SE Programmer Exam, OCP Java SE 6 Programmer Practice Exams is filled with more than 260 realistic practice questions to prepare you for this challenging exam. To help you understand this material, in-depth explanations of both the correct and incorrect answers are included for every question. This practical guide covers all official objectives for Exam 310-065 and is the perfect companion to SCJP Sun Certified Programmer for Java 6 Study Guide. Covers all OCP Java SE 6 Programmer exam topics, including: Declarations and Access Control Object Orientation Assignments Operators Flow Control, Exceptions, and Assertions Strings, I/O, Formatting, and Parsing Generics and Collections Inner Classes Threads Development"--Provided by publisher
Machine generated contents note: Chapter 1: Self-Assessment Test 1 -- Chapter 2: Self-Assessment Test 2 -- Chapter 3: Practice Exam 1 -- Chapter 4: Coding Exercises -- Chapter 5: Practice Exam 2 -- Chapter 6: Practice Exam 3 -- Chapter 7: Practice Exam 4 -- Appendix: Objectives Index
Includes index
1
Keywords: Java (Computer program language) -- Examinations -- Study guides